Criminalisation of clients: reproducing vulnerabilities for violence and poor health among street-based sex workers in Canada—a qualitative study. Issue 6 (2nd June 2014) - Krüsi, A; Pacey, K; Bird, L; Taylor, C; Chettiar, J; Allan, S; Bennett, D; Montaner, J S; Kerr, T; Shannon, K
Abstract : Objectives: To explore how criminalisation and policing of sex buyers (clients) rather than sex workers shapes sex workers' working conditions and sexual transactions including risk of violence and HIV/sexually transmitted infections (STIs). Design: Qualitative and ethnographic study triangulated with sex work-related violence prevalence data and publicly available police statistics. Setting: Vancouver, Canada, provides a unique opportunity to evaluate the impact of policies that criminalise clients as the local police department adopted a sex work enforcement policy in January 2013 that prioritises sex workers' safety over arrest, while continuing to target clients. Participants: 26 cisgender and 5 transgender women who were street-based sex workers (n=31) participated in semistructured interviews about their working conditions. All had exchanged sex for money in the previous 30 days in Vancouver. Outcome measures: Thematic analysis of interview transcripts and ethnographic field notes focused on how police enforcement of clients shaped sex workers' working conditions and sexual transactions, including risk of violence and HIV/STIs, over an 11-month period postpolicy implementation (January–November 2013). Results: Sex workers' narratives and ethnographic observations indicated that while police sustained a high level of visibility, they eased charging or arresting sex workers and showed increased concern for their safety. However, participants' accounts and police statistics indicated continued police enforcement of clients. This profoundly impacted the safety strategies sex workers employed. Sex workers continued to mistrust police, had to rush screening clients and were displaced to outlying areas with increased risks of violence, including being forced to engage in unprotected sex. Conclusions: These findings suggest that criminalisation and policing strategies that target clients reproduce the harms created by the criminalisation of sex work, in particular, vulnerability to violence and HIV/STIs. The current findings support decriminalisation of sex work to ensure work conditions that support the health and safety of sex workers in Canada and globally.